2013
DOI: 10.1152/jn.00005.2013
|View full text |Cite
|
Sign up to set email alerts
|

Impaired foot-force direction regulation during postural loaded locomotion in individuals poststroke

Abstract: Following stroke, hemiparesis results in impaired motor control. Specifically, inappropriate direction of foot-forces during locomotion has been reported. In our previous study (Liang and Brown 2011) that examined poststroke foot-force direction during a seated, supported locomotor task, we observed that foot-force control capabilities were preserved poststroke. In this current study, we sought to better understand the mechanisms underlying the interaction of locomotor and postural control as an interactive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 47 publications
4
17
0
Order By: Relevance
“…The lack of difference on the measured gait parameters between feedback conditions demonstrates that average spatial/temporal aspects of walking were unchanged, despite reduced AP and ML trunk translation in space. This is consistent with the idea that cyclic behavior of the legs, path consistency and upright orientation are separate tasks during walking [7,27,50], and demonstrates that path consistency can be modified independent of changes to the average walking pattern. The implication for rehabilitation is that isolated functional impairments in COM translation control may be effectively improved during walking using concurrent visual FB.…”
Section: Discussionsupporting
confidence: 88%
“…The lack of difference on the measured gait parameters between feedback conditions demonstrates that average spatial/temporal aspects of walking were unchanged, despite reduced AP and ML trunk translation in space. This is consistent with the idea that cyclic behavior of the legs, path consistency and upright orientation are separate tasks during walking [7,27,50], and demonstrates that path consistency can be modified independent of changes to the average walking pattern. The implication for rehabilitation is that isolated functional impairments in COM translation control may be effectively improved during walking using concurrent visual FB.…”
Section: Discussionsupporting
confidence: 88%
“…Evidence suggested that addition of postural control could interfere with locomotor output in people post-stroke during a standing, non-seated pedaling task [16]. Thus, further research must be conducted to determine whether inappropriate shear forces will be revealed under non-seated, postural demanding conditions, where subjects have to actively control for posture [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Massion suggests that the neural control of posture and locomotion are separate, but interacting controllers for normal walking [8]. Previously, Liang and Brown suggested that Massion’s model may be altered poststroke, such that the requirement for generating vertical support forces during locomotion interferes with regulation of foot force direction [9]. The current study suggests reducing the vertical support requirement of locomotion with BWS may result in less interference of postural control centers on locomotor control.…”
Section: Discussionmentioning
confidence: 68%